Images of Spatial Representations in Charles Dickens’s New York - Lin, Tzu Yu Allison (Journal of History Culture and Art Research, 2013)
Abstract Agnes Calder claims that Charles Dickens came back from America, ’heartily disillusioned’ (Dickens 8). In this paper, through reading American Notes (1842), I see the image of spatial representation in the city of New York. On the surface, the city shows Dickens’s eye of observation, revealing the dark side of the city. And yet, Dickens’s writing expresses more than what he sees. Dickens’s image of New York, I argue, is not only a ’realistic’ account of what things look like, but a true realisation of how he feels about himself, and about the country in which he was situated in.